Peran ESG (Enviromental, Sosial, and Governance) Dalam Meningkatkan Kualitas Keputusan Investasi Pada PT Pertamina (Persero) - Maharani Adi Pamasa; Hanna Nelin Solossa; Titiek Rachmawati (Nirta Learning Centre, 2026)
This study aims to analyze the role of Environmental, Social, and Governance (ESG) in improving the quality of investment decisions at PT Pertamina (Persero). In the modern business environment, ESG has become a critical framework as it integrates financial and non-financial aspects, particularly sustainability and risk considerations. This research employs a qualitative descriptive approach using secondary data derived from annual reports and sustainability reports.The findings indicate that ESG implementation enhances corporate transparency, strengthens governance structures, and supports the identification and mitigation of environmental and social risks. Furthermore, ESG contributes to increased investor confidence and promotes long-term value creation. Therefore, ESG serves as a strategic foundation in generating high-quality, sustainable, and responsible investment decisions.